A remote monitoring system of Potato Growing Conditions in urban crops - Calla, Nathali; Barrios-Aranibar, Dennis (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
The text addresses the impact of overpopulation climate change, and rising food prices on food security, highlighting urban agriculture as an innovative solution. While this method allows for food production in small spaces, it demands time and commitment, which can be challenging for busy individuals. Agriculture 4.0 employs satellites, robotics, and AI to optimize crop monitoring, conserve water, and eliminate insecticides. The proposed system includes data collection, cloud transmission, and user-friendly interpretation, featuring humidity and temperature sensors linked to an ESP32 microcontroller, a real-time database, and a web platform for control. Results indicate improved care and growth of potato plants by maintaining optimal conditions. The system is user-friendly, scalable, and future research aims to integrate mobile robots for broader applications.